Studies on breeding market pigs by crossing Duroc and Poland with Minnesota No. 1. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2012)
There has been much discussion in Kansas as to the desirability of using the Minnesota No. 1 breed of swine for crossing on other breeds. Consequently a few years ago one of these boards was secured for this purpose. In order to get as true a value of crossing as possible, it was planned in this experiment to double mate the sows. That is, to breed them to a boar of their own breed first and immediately after to breed them again to the Minnesota No. 1 boar. In this way it was theoretically possible to get in the same littler cross bred pigs and pure bred pigs. The plan involved further the separating of these pure bred and cross bed pigs and feeding them out for market in separate groups.
Keywords: Swine; Duroc; Poland; Gain